Teacher Candidates’ Views on the Zero Waste Project - Erten, Sinan; Atmaca, Ayşe Ceren (Department of Science Education, Universitas Sultan Ageng Tirtayasa, 2021)
This case study was carried out to determine the opinions of prospective science teachers about zero waste project. The study group of the research consists of 67 prospective teachers studying in the science education department at one university in Konya, Turkey. When the research results are examined, it is seen that the awareness of the science teacher candidates about the purpose and scope of the zero waste project is not sufficient. Most of the teacher candidates experience a lack of information about the zero waste project. The teacher candidates, who stated that they did not participate in any scientific activity related to the zero waste project, do not believe that this project has achieved its purpose. The results of the research show that informing about the zero waste project is not enough, many teacher candidates will graduate without having sufficient awareness. As researchers, we think that information about the scope, purpose and implementation steps of the zero waste project should be included more in education curricula, TV programs and scientific activities.